Nitrogen assimilation under different nitrate nutrition in Tunisian durum wheat landraces and improved genotypes. (1st November 2020) - Ayadi, Sawsen; Jallouli, Salma; Landi, Simone; Capasso, Giorgia; Chamekh, Zoubeir; Cardi, Manuela; Paradisone, Valeria; Lentini, Marco; Karmous, Chahine; Trifa, Youssef; Esposito, Sergio
Abstract: The effects of nitrate were studied in wheat varieties grown in hydroponic culture: two landraces (Azizi and Bidi), and two improved genotypes (Om Rabiaa and Khiar) from Tunisia. Nitrogen (N) supply generally induced an increase in plant height in all varieties, albeit to a different extent; interestingly, landraces exhibited the same N Uptake Efficiency (NUpE) as other varieties, and a lower Nitrogen Utilization Efficiency (NUtE); in contrast, improved genotypes exhibit a better NUtE at high N. Nitrate reductase activity (NRA) was sensibly and constitutively higher in the improved genotypes in the roots, while NRA was strongly influenced by nitrate supply in the leaves of Bidi landrace. Glutamine synthetase (GS) activity was similar in all varieties studied, in contrast, ferredoxin-glutamate synthase (Fd- GOGAT) activity and occurrence were increased by nitrate. Intriguingly, glutamate dehydrogenase (GDH) activity followed an opposite behaviour with respect to GOGAT. Glucose-6P-dehydrogenase (G6PDH), which provides reductants for N assimilation, increased in roots upon nitrate supply, but the different plastidial and cytosolic isoforms differently changed in the different varieties studied. The data suggest that landraces present higher metabolic flexibility as compared with improved cultivars; therefore, the metabolic changes observed could be suitable for the identification of factors limiting the NUtE.